Unusual responses to PCSK9 inhibitors in a clinical cohort utilizing a structured follow-up protocol - Bruce A. Warden; Joshua R. Miles; Carlota Oleaga; Om P. Ganda; P. Barton Duell; Jonathan Q. Purnell; Michael D. Shapiro; Sergio Fazio (Elsevier, 2020)
Objective: To characterize unusual responses to PCSK9 inhibitor (PCSK9i) therapy in a real-world setting, given their extremely low prevalence in clinical trials. Methods: A retrospective study of patients seen in a structured academic PCSK9i clinic who had LDL-C measurements before and after initiation of PCSK9i (up to 12 months). Unusual response was defined as: (1) no response: no changes in LDL-C level at all time points; (2) delayed response: <30% LDL-C reduction by the third dose, but achieving this threshold at a later time; (3) reduced response: <30% LDL-C reduction at all time points; and (4) lost response: ≥30% LDL-C reduction by the third dose, but displaying <30% reduction at a later time. Results: Of the 411 patients meeting inclusion criteria, 54 were initially classified as unusual responders. After excluding those not adherent to prescribed interventions, 31 patients (7.5%) were classified as true unusual responders. These included: 2 with no response, 12 with delayed response, 3 with reduced response, 6 with delayed or reduced response, 4 with lost response, and 4 with delayed and lost response. Response to PCSK9i therapy at all time points revealed higher on-treatment LDL-C values (94-100 vs. 47-51 ​mg/dL, p ​< ​0.001) and lower degree of percent reduction in LDL-C (23.3-34% vs. 61.1-64.5%, p ​< ​0.001) in the unusual versus usual responders. Lipoprotein (a) (Lp[a]) values were consistently higher in the unusual responders (81-92.5 vs. 28.5-52 ​mg/dL, p ​< ​0.01). Fold change in post-versus pre-treatment PCSK9 plasma results was similar between the two cohorts (p ​> ​0.05), suggesting that unusual responses were not due to insufficient plasma PCSK9 blockade. Multiple logistic regression analysis identified clinical FH (OR 2.9, 95% CI 1.27-7.24) and no ezetimibe therapy (OR 0.334, 95% CI 0.150-0.728) as factors related to true unusual response. Conclusions: Unusual responses to PCSK9i in a clinical cohort are more common than reported in clinical trials. Of the suspected unusual responders, nearly half were the result of adherence issues, and thus careful medication reconciliation should be the first step in diagnosing an unusual response.